DFT Study on Adsorption of Acetone and Toluene on Silicene - Lam, Pham Trong; Luong, Ta Thi; On, Vo Van; An, Dinh Van (VNU Journal of Science: Mathematics - Physics, 2020)
In this work, we investigated the adsorption mechanism of acetone and toluene on the surface of silicene by the quantum simulation method. The images of the potential energy surfaces for different positions of the adsorbate on the silicene surface were explored by Computational DFT-based Nanoscope tool for determination of the most stable configurations and diffusion possibilities. The charge transfer in order of 0.2 – 0.3 electrons and the tunneling gap opening of 18 – 23 meV due to acetone and toluene, respectively, suggest that silicene is considerably sensitive with these VOCs and can be used as the material in the fabrication of reusable VOC sensors.